Peri-Implant Tissue Adaptation after Implant Rehabilitation with Shoulderless Abutments with 24 Months of Follow-Up - Luca Casula; Alex Gillone; Davide Musu (Case Reports in Dentistry)
An 11-year-old girl presented with agenesis of the maxillary lateral incisors. Orthodontic treatment was performed to close the midline diastema and create adequate space between the central incisors and canines to replace the missing maxillary lateral incisors on both sides. Two-piece implants were placed, and shoulderless abutments were prepared following the “biologically oriented preparation technique” (BOPT) protocol. The soft tissues were allowed to heal directly on the prosthetic emergence profile of the interim crown restorations after implant exposure. Two months later, the gingival tissue adapted to the prosthetic components in a specular manner. No complications were noted at 24 months. The BOPT protocol, originally described for natural teeth, may be applied to dental implants with shoulderless abutments.